To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius) - Anichtchenko, Alexander; Kirschenhofer, Erich (Zootaxa, 2017)
The species of subgenus Pseudochlaeniellus Jeannel, 1949 (Carabidae: Chlaenius) from Oriental region are revised. The following new synonyms and new combinations are proposed: C. (Pseudochlaeniellus) puncticollis Dejean, 1826 = C. (P.) panjabensis Kirschenhofer, 1998 syn. n.; C. (P.) germanus Chaudoir, 1876 = Chlaenius laevipennis Chaudoir, 1876: 196 syn. n. = C. (P.) buriensis Kirschenhofer 1998 syn. n.; C. (P.) sobrinus Dejean, 1826 = C. (P.) callichloris Bates, 1873 syn. n. = C. (P.) ladon Kirschenhofer, 1998 syn. n.; C. (P.) lomsakensis Kirschenhofer, 1998 = C. (P.) farkaci Kirschenhofer, 2005 syn. n. = C. (P.) viangchanensis Kirschenhofer, 1998 syn. n.; C. (P.) celer Chaudoir, 1876 = C. (P.) chitwanensis Kirchenhofer, 2005 syn. n.; C. (P.) lucasi Peyron, 1858 comb. n. = C. (P.) irakensis Jedlicka, 1959 syn. n.; C. (P.) nigrosuturatus Mandl, 1978 transferred to subgenus Chlaeniellus Reitter, 1908. Key to species and images of habitus and genitalia for all species provided.